Dual-channel functional electrical stimulation improvements in speed-based gait classifications - Springer S (Dove Medical Press, 2013)
Shmuel Springer,1,2 Yocheved Laufer,1 Meni Becher,1,2 Jean-Jacques Vatine3,41Department of Physical Therapy, Faculty of Social Welfare and Health Sciences, University of Haifa, Haifa, 2Clinical Department, Bioness Neuromodulation, Ra'anana, 3Outpatient and Research Division, Reuth Medical Center, Tel Aviv, 4Department of Rehabilitation Medicine, Sackler Faculty of Medicine, Tel-Aviv University, Tel-Aviv, IsraelBackground: Functional electrical stimulation (FES) is becoming an accepted treatment method for enhancing gait performance in patients who present with gait difficulties resulting from hemiparesis. The purpose of this study was to test whether individuals with hemiparesis who have varied gait speeds, which place them in different functional categories, benefit to the same extent from the application of FES.Methods: Thirty-six subjects with chronic hemiparesis demonstrating foot-drop and deficits in knee and/or hip control were fitted with a dual-channel FES system activating the dorsiflexors and hamstring muscles. Gait was assessed during a 2-minute walk test with and without stimulation. A second assessment was conducted after 6 weeks of daily use. Analysis was performed with the subjects stratified into three functional ambulation classes according to their initial gait categories.Results: The dual-channel FES improved the gait velocity of all three subgroups. No minimal gait velocity was required in order to gain benefits from FES. For example, subjects with limited household ambulation capabilities improved their gait speed by 63.3% (from 0.30 ± 0.09 m/sec to 0.49 ± 0.20 m/sec; P < 0.01), while subjects with functional community ambulation capabilities improved their gait speed by 25.5% (from 0.90 ± 0.11 m/sec to 1.13 ± 0.22 m/sec; P < 0.01).Conclusion: Dual-channel FES positively affects gait velocity in patients with chronic hemiparesis, regardless of their initial gait velocity. Furthermore, gait velocity gains may be large enough to change an individual's ambulation status to a higher functional category.Keywords: hemiparesis, functional electrical stimulation, gait velocity, ambulation